2019
DOI: 10.1186/s12872-018-0981-3
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital and post-discharge outcomes of pediatric acute myocarditis underwent after high-dose steroid or intravenous immunoglobulin therapy

Abstract: BackgroundHigh-dose steroids and intravenous immunoglobulin (IVIG) are controversial treatments for pediatric patients with acute myocarditis. This study aimed to investigate their efficacies in the Taiwanese pediatric population.MethodsThis study evaluated 5563 acute myocarditis patients from the Taiwan’s National Health Insurance Research Database and identified 1542 pediatric patients hospitalized for acute myocarditis between January 1, 2001 and December 31, 2011. The exclusion criteria were age of > 11 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…However, the study in the pediatric population had limitations of lack of a matched control group and the fact that myocarditis patients already had high survival rates. A recent study evaluated 1542 pediatric patients who were hospitalized for acute myocarditis . They were divided into three groups: Those receiving neither steroid nor IVIG; those receiving high‐dose steroid alone; and those receiving IVIG alone.…”
Section: Follow‐up and Restrictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the study in the pediatric population had limitations of lack of a matched control group and the fact that myocarditis patients already had high survival rates. A recent study evaluated 1542 pediatric patients who were hospitalized for acute myocarditis . They were divided into three groups: Those receiving neither steroid nor IVIG; those receiving high‐dose steroid alone; and those receiving IVIG alone.…”
Section: Follow‐up and Restrictionsmentioning
confidence: 99%
“…A recent study evaluated 1542 pediatric patients who were hospitalized for acute myocarditis. 83 They were divided into three groups: Those receiving neither steroid nor IVIG; those receiving high-dose steroid alone; and those receiving IVIG alone.…”
Section: Statement For Eligibility and Disqualification Recommendationsmentioning
confidence: 99%
“… 7 Although contemporaneous studies showed clinical and immunophenotypic differences between Kawasaki’s disease and MIS-C, 8-10 findings of myocarditis in many patients with MIS-C also supported treatment with IVIG, given its use in clinical practice for viral myocarditis. 11 , 12 Features of cytokine storm led to the use of dexamethasone in patients with acute Covid-19, 13 and the frequent concurrent finding of a severe shock-like presentation in patients with MIS-C 14 probably encouraged the use of glucocorticoids, in varying doses. 15 …”
mentioning
confidence: 99%
“…In total, the summary covers 1,891 children diagnosed with myocarditis (Table 1) [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. It is, therefore, a rare disease.…”
Section: Resultsmentioning
confidence: 99%